Tutorial: Theoretical Considerations When Planning Research on Human Factors in Lighting. Issue 2 (3rd July 2019) - de Kort, Yvonne A. W.
ABSTRACT: Research on human functioning is notoriously difficult. This particularly holds for the study of light effects, at least if one wants to go beyond establishing that changes in light "have an effect" and understand why this effect occurs—in other words, if one wants to make causal inferences about the mechanism behind it. The latter is, of course, crucial for generalizing insights and being able to use them effectively in other contexts. The culmination of many decades of research has taught us that light affects psychological functioning in numerous ways and through various pathways. This implies that, regardless of the investigator's particular interests in either of those mechanisms, generally all will be at play, simultaneously, for participants in any lighting study. The present tutorial aims to address this complexity and how to deal with it by concisely describing the most important pathways that we currently are aware of. Such awareness is important both in contemplating the design and methodology of a study and in interpreting results from other studies and generalizing them to a particular application or light design.